2017
DOI: 10.17576/jsm-2017-4610-32
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of γ-Fe2O3, Fe3O4 and Copper Doped Fe3O4 Nanoparticles by Sonochemical Method

Abstract: Nanoparticles of undoped and copper doped with Fe 3 O 4 of three concentrations (0.5, 1.0 and 1.5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 23 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…3 and 4). The energy of band gap for Zn-Fe3O4Nps was found to be 1.9ev (direct band gap) and 1.3eV (indirect band gap), which is smaller than bulk Fe3O4NPs [18]. The outcome confirmed that zinc metal ion plays a significant role to reduce the energy band gap of the magnetite nanoparticles.…”
Section: Uv-vis Absorption Spectramentioning
confidence: 65%
“…3 and 4). The energy of band gap for Zn-Fe3O4Nps was found to be 1.9ev (direct band gap) and 1.3eV (indirect band gap), which is smaller than bulk Fe3O4NPs [18]. The outcome confirmed that zinc metal ion plays a significant role to reduce the energy band gap of the magnetite nanoparticles.…”
Section: Uv-vis Absorption Spectramentioning
confidence: 65%
“…Symposium of Materials Science and Chemistry III However, as shown in Fig. 2 (b) the agglomeration of Fe3O4 was observed by the Cu 1% addition due to the strong interaction of Fe3O4 magnetic particles [24]. The presence of metal on the nanocomposite will be increase agglomeration [25].…”
mentioning
confidence: 93%